The challenging journey of cervical cancer diagnosis and treatment at the second largest hospital in Indonesia - Brahmana Askandar Tjokroprawiro; Khoirunnisa Novitasari; Wita Saraswati; Indra Yuliati; Renata Alya Ulhaq; Hanif Ardiansyah Sulistya (Elsevier, 2024)
Objectives: Cervical cancer is a major health concern in developing countries. Access to preventive measures is limited in low- and middle-income countries, and cervical cancer is often identified at an advanced stage of the disease. In this study, we aimed to investigate when patients were first diagnosed and received treatment at a large hospital in Indonesia. Methods: Data were collected using a questionnaire from outpatient visits and descriptively analyzed. Totally, 215 cervical cancer patients being treated at the Dr. Soetomo Academic Hospital's gynecological oncology outpatient clinic in Indonesia between August and October 2022 were included. Results: Most patients were 51-60 years old (36.3 %), housewives (87 %), and had an elementary school education level (50 %). Most (88.4 %) admitted they were unaware about cervical cancer prevention, and 85.6 % never underwent screening. Most cervical biopsies were performed at primary hospitals (42.3 %). Fear of cancer treatment was the most frequent reason for patients arriving late at tertiary hospitals (50 %). Treatment delays occurred because patients had to visit two healthcare facilities before visiting a tertiary hospital (47.4 %). Most patients were diagnosed with stage III cancer (38.1 %), and chemotherapy was administered as the first-line therapy (96.3 %). Most patients (51.2 %) received their first therapy >12 months after initial symptom onset. Conclusions: Most cervical cancer patients were diagnosed at a late stage owing to a lack of information regarding early symptoms and irregular screenings. Treatment was delayed owing to social barriers. Therefore, the government should have more strict policies to implement cervical cancer detection and prevention.